ENVIRONMENTAL DEGRADATION OF THE COASTAL ZONE OF THE WEST PART OF NESTOS RIVER DELTA, N.GREECE - Xeidakis, G.; Georgoulas, A.; Kotsovinos, N.; Delimani, P.; Varaggouli, E. (Bulletin of the Geological Society of Greece, 2010)
The coastal zone is a transitory zone between land and sea. Due to its importance to man, not only for its high food production but also for recreation, sea transportation and industrial activities, coastal zone receives high environmental pressure from him. This paper deals with degradation phenomena of the coastal zone in the west section of the River Nestos Delta, North Aegean Sea, with special stress on the geomorphological changes in the coastline. The length of the coastline in this part of river Nestos Delta (the Kavala- Chrisoupoli part), from Nea Karvali village to the west, up to the river mouth to the east, is around 35 km long. This section constitutes the biggest and more extended sector of the Nestos Delta; it is the section where the main course and the various branches of the river were located, in the past. Along the coastal zone of this section of the delta many lagoons, sand bars, spits, barrier islands, washover fans, etc. were developed in its geologic past. Some of these geoforms still exist, but the majority of them have been destroyed by physical and/or anthropogenic interventions. Two of the last interventions are the diversion and entrenchment of the river to the east, in early 50’s and the construction of two high dams in the river course inland, in 2000. These human interventions deprived this land of flooding waters and sediments resulting in: (a) drying of most of the river channels and courses crossing this area of the river’s delta, (b) erosion of the coastal landforms and retreat of the shoreline in the majority of the delta coasts. There are, of course, a few places along the coastline where deposition and accretion are still taking place. In more detail, along the coastline taken into consideration in the present paper, one can meet: • stretches with high erosion rates, like the Akroneri Cape (spit), the inner coastline of Keramoti bay (Kokala -Piges coast), the Monastiraki coastline, etc, • stretches with high accretion rates like the Keramoti peninsula/spit, and • stretches at equilibrium or low rate of change like the barrier (spit) west of Akroneri Cape up to Nea Karvali coast and a short stretch of the coastline south-east of Keramoti peninsula. Comparing the Delta coastline of 1945 (from available aerial photographs) and the coastline of 2002 (from high resolution satellite images), before the construction of the Thisavros and Platanovrisi high dams (period 1945-2002), it has been estimated that: 88% of the delta and the adjacent coastlines has been accreted while only 12% has been eroded. In other words, there was a surplus of accretion by 76% and the delta was procreated. Comparing the Delta coastline of 2002 (from high resolution satellite images) and the coastline of 2007 (from high resolution D-GPS field measurements), after the construction of the dams (period 2002-2007), it has been estimated that: only 39% of the delta and the adjacent coastlines has been accreted while 61% has been eroded. In other words, there was a surplus of erosion by 22% and the delta began to retreat. This was due to Δελτίο της Ελληνικής Γεωλογικής Εταιρίας, 2010 Bulletin of the Geological Society of Greece, 2010 Πρακτικά 12ου Διεθνούς Συνεδρίου Proceedings of the 12th International Congress Πάτρα, Μάιος 2010 Patras, May, 2010 the great reduction (by almost 80%) of the river’s sediment load reaching to the sea. Thus, up to 2002, or so, the balance accretion – erosion in the whole delta coastline was positive, whereas after 2002 the erosion and retreat predominates in the delta’s coastline. The prevention of sediments and fresh water flooding in the delta area, has also affected the crops production in the fields in the vicinity of the delta as well as the fish output in the lakes and lagoons of the coastal zone.